2018
DOI: 10.1111/jphp.12913
|View full text |Cite
|
Sign up to set email alerts
|

MiR-505 mediates methotrexate resistance in colorectal cancer by targeting RASSF8

Abstract: MiR-505 mediated MTX resistance, propagation, cell cycle and metastasis by targeting RASSF8 in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Rassf8 is found both in the nucleus and cell membrane 33 . Rassf8 is related to the cell cycle, accelerates apoptosis, and restrains migration and invasion 52 . Overexpression of Rassf8 induces G0/G1 arrest, apoptosis, and downregulation of Cyclin D1 downstream of the WNT/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Rassf8 is found both in the nucleus and cell membrane 33 . Rassf8 is related to the cell cycle, accelerates apoptosis, and restrains migration and invasion 52 . Overexpression of Rassf8 induces G0/G1 arrest, apoptosis, and downregulation of Cyclin D1 downstream of the WNT/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the present years, several studies have explored the role of miR-505 in the development of various cancers (Y. Chen et al, 2018;Liu et al, 2018;. The results of these studies have suggested that the overexpression of miR-505 suppressed the proliferation of many different types of tumors ( Y.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs participate in diverse molecular and cellular processes, such as cellular migration/invasion, cell growth, apoptosis and signal transduction. MiRNAs dysregulation is a hallmark of many cancers, including glioblastoma, and they can be classified into tumour‐suppressive miRNAs and onco‐miRNAs . For example, miRNA‐744 expression is strongly repressed in glioblastoma, causing elevated transforming growth factor 1 beta (TGFB1) and dishevelled 2 (DVL2) expression and increased tumour cell migration .…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs dysregulation is a hallmark of many cancers, including glioblastoma, and they can be classified into tumour-suppressive miRNAs and onco-miRNAs. [24][25][26][27][28] For example, miRNA-744 expression is strongly repressed in glioblastoma, causing elevated transforming growth factor 1 beta (TGFB1) and dishevelled 2 (DVL2) expression and increased tumour cell migration. [29] In contrast, up-regulation of miRNA-21 in glioblastoma is associated with suppression of phosphatase and tensin homolog (PTEN), as well as programmed cell death 4 (PDCD4) expression, causing enhancement of cell survival and inhibition of apoptosis.…”
Section: Introductionmentioning
confidence: 99%